Humas dan Media Sosial sebagai Seni Membangun Reputasi Sekolah di Era Post Truth: Systematic Literature Review - Ridwan Abdullah; Sep Arinda Risa Kamal; Hariyani Prasetyaningtyas; Unifah Rosyidi; Muh. Takdir (Journal on Education, 2025)
In the post-truth era, social media plays a strategic role in shaping public perceptions of school reputation. This article analyzes the role of public relations (PR) and social media as strategic tools for building school reputation through a Systematic Literature Review (SLR) approach. Findings indicate that effective PR leveraging social media can create positive narratives supporting school image, enhancing public trust, and mitigating the impact of fake news. Social media functions not only as a communication channel but also as a collaboration tool among schools, students, and communities. The article concludes the importance of digital literacy, rapid response, and data-driven approaches in managing school reputation in the fast-paced information era.